Anti-tumor activity of Simarouba glauca on Ehrlich ascites carcinoma in mice - Ramalingam, Sivakumar; Renuka, Saravanan (Bangladesh Journal of Pharmacology, 2025)
This study aimed to evaluate the anti-cancer potential of the ethanolic extract of Simarouba glauca leaf in Ehrlich ascites carcinoma-bearing Swiss albino mice. Ehrlich ascites carcinoma was induced by intraperitoneal injection of 1 × 10⁶ viable cells in each mouse. The extract (150 or 300 mg/kg) was administered as test, and standard drug 5-fluorouracil (20 mg/kg) as a positive control. Anti-tumor activity was assessed through changes in body weight, mean survival time, hematological parameters, hepatic glycoproteins, and antioxidant status. S. glauca extract significantly reduced tumor burden, improved mean survival time, normalized hemoglobin and erythrocyte counts, elevated antioxidant enzyme levels, and decreased liver glycoproteins. The 300 mg/kg dose showed superior efficacy compared to the lower dose and 5-fluorouracil. These findings suggest that S. glauca extract exhibits anti-tumor effects, likely mediated through antioxidant and immuno-modulatory mechanisms.